자산가격의 오류는 인플레이션의 착각 때문인가? - 이봉수 (13777, 2014)
We examine whether the observed negative relations between stock returns and inflation and between housing returns and inflation can be explained by the inflation illusion hypothesis. We identify the mispricing component in asset prices (i.e., stock price